2017
DOI: 10.1186/s12985-017-0883-5
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of an improved DNA-launched infectious clone of duck hepatitis a virus type 1

Abstract: BackgroundDNA-launched infectious system is a useful tool with high rescue efficiency that allows the introduction of mutations in specific positions to investigate the function of an individual viral element. Rescued virus particles could be harvested by directly transfecting the DNA-launched recombinant plasmid to the host cells, which will reduce labor and experimental cost by skipping the in vitro transcription assay.MethodsA total of four overlapping fragments covering the entire viral genome were amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Secondly, we speculated that the organs of healthy ducklings with low levels of ILF2 might be preferentially infected with DHAV-1 since ILF2 inhibits DHAV-1 replication. Previous studies have shown that DHAV-1 preferentially infects liver tissue since the viral genome could only be detected in liver as early as 1 hpi [ 37 ]. Therefore, the highly low initial transcription levels of ILF2 in liver tissue (Figure 7 A) might contribute to the hepatotropism of DHAV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we speculated that the organs of healthy ducklings with low levels of ILF2 might be preferentially infected with DHAV-1 since ILF2 inhibits DHAV-1 replication. Previous studies have shown that DHAV-1 preferentially infects liver tissue since the viral genome could only be detected in liver as early as 1 hpi [ 37 ]. Therefore, the highly low initial transcription levels of ILF2 in liver tissue (Figure 7 A) might contribute to the hepatotropism of DHAV-1.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA viruses, the HamRz and HdvRz as self-cleaving RNA ribozyme elements had been introduced into DNA-launched infectious cDNA clones to successfully improve the rescue efficiency [25,26]. In this study, the two self-cleaving elements were added at both termini of the viral genomic cDNA to generate a DNA-launched infectious clone of DAstV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were examined using IFA every five generations as previous described [26]. At 60 hpt, the transfected BHK-21 cells and the infected DEF cells were washed three times with phosphate-buffered saline (PBS, 8.1 mM Na 2 HPO4, 1.5 mM KH 2 PO 4 , 140 mM NaC1, 3.0 mM KC1, pH 7.2) and then fixed by a mixture of acetone and formaldehyde (1:1) for 20 min at room temperature.…”
Section: Detection Of the Rescued Virus By Immunofluorescence Assay (mentioning
confidence: 99%
“…The RNA-launched infectious clone of DHAV-1 named pR-DHAV-1 (Figure 1C) was previously established based on the strain LY0801 (accession no. FJ436047) [27].…”
Section: Methodsmentioning
confidence: 99%